Responses of Glossina fuscipes fuscipes to visually attractive stationary devices baited with 4-methylguaiacol and certain repellent compounds in waterbuck odour. - Njelembo J Mbewe; Rajinder K Saini; Janet Irungu; Abdullahi A Yusuf; Christian W W Pirk; Baldwyn Torto (Public Library of Science (PLoS), 2019)
Background A blend of compounds (pentanoic acid, guaiacol, δ-octalactone and geranylacetone) identified in waterbuck (Kobus defassa) body odour referred to as waterbuck repellent compounds (WRC) and a synthetic repellent 4-methylguaiacol have previously been shown to repel tsetse flies from the morsitans group. However, these repellents have not been evaluated on palpalis group tsetse flies. In this study, we evaluated the effect of these repellents on catches of Glossina fuscipes fuscipes (major vector of human sleeping sickness) in biconical traps and on sticky small targets which are visually attractive to palpalis group flies. The attractive devices were baited with different doses and blends of the repellent compounds. We also assessed the effect of removal of individual constituents in the synthetic blend of WRC on catches of G. f. fuscipes. Methodology/principal findings The study was conducted in western Kenya on four islands of Lake Victoria namely Big Chamaunga, Small Chamaunga, Manga and Rusinga. The tsetse fly catches from the treatments were modeled using a negative binomial regression to determine their effect on catches. In the presence of WRC and 4-methylguaiacol (released at ≈2 mg/h and ≈1.4 mg/h respectively), catches of G. f. fuscipes were significantly reduced by 33% (P<0.001) and 22% (P<0.001) respectively in biconical traps relative to control. On sticky small targets the reduction in fly catches were approximately 30% (P<0.001) for both 4-methylguiacol and WRC. In subtractive assays, only removal of geranylacetone from WRC significantly increased catches (by 1.8 times; P <0.001) compared to the complete blend of WRC. Conclusions/significance We conclude that WRC and 4-methylguaiacol reduce catches of G. f. fuscipes at stationary visually attractive traps and suggest that they may serve as broad spectrum repellents for Glossina species. We recommend further studies to investigate the effects of these compounds on reduction of G. f. fuscipes attracted to human hosts as this may lead to development of new strategies of reducing the prevalence and incidence of sleeping sickness.